ANALISIS MENGENAI LUBANG-LUBANG KORUPSI DI SEKTOR BEA DAN CUKAI - Ari fin; Arif Nugroho (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
Corruption in customs and excise sector full with political and economic motives, the perpetrator involvels Customs’ official and implementing officer at both central and local level. The main characteristic of corruption in the sector is to deliberately slow down or delay the document processing and inspection. This study aimed to analyzed : (i) the risks and opportunities for corruption in the sector of customs and excise ; an (ii) the prevention and eradication of corruption in the sector of customs and excise. The writer used a normative legal research method with legislation approach. In order to produce representative thought, the writer or used the relative theory approach ( deterrence ) created by cesare beccaria and Jeremy Bentham, containing a core of basic justification that the presence of a criminal lies on the objectives. The research results showed that the anti-corruption program was implemented by mapping or identification of sources of corruption. Combating corruption is not just thourgh prosecution and prevention, but a role model is highly needed.